1982
DOI: 10.1093/oxfordjournals.jbchem.a133729
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Immunological Properties and Amino Acid Sequences of Three Lysozymes from Peking-Duck Egg White

Abstract: Three lysozymes (DLs-1, -2, and -3) were purified from Peking-duck egg white by adsorption on CM-Sephadex C-25 resin, followed by CM-Sephadex C-25 and Sephadex G-50 column chromatographies. The three enzymes each moved as a single band, but showed different electrophoretic mobilities, on disc-polyacrylamide gel electrophoresis at pH 4.1. Final yields of DL-1, DL-2, DL-3 were 18.2%, 22.0%, and 6.0%, respectively, from the crude material adsorbed on CM-Sephadex resin. The enzymatic activities of DL-1, DL-2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…It may be due to the differences of amino acid composition between these two Lzs. Compared with cLz, the contents of arginine, valine and tyrosine residue dLz were higher by a few residues, while those of aspartic acid, alanine and phenylalanine residues were lower by two, one and two residues, respectively (Kondo, 1982). The difference of arginine content in both Lz was also presented in other report.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…It may be due to the differences of amino acid composition between these two Lzs. Compared with cLz, the contents of arginine, valine and tyrosine residue dLz were higher by a few residues, while those of aspartic acid, alanine and phenylalanine residues were lower by two, one and two residues, respectively (Kondo, 1982). The difference of arginine content in both Lz was also presented in other report.…”
Section: Resultssupporting
confidence: 66%
“…Thus, these two bands were confirmed as dLz. The difference of these two peaks may be due to the multiple forms of dLz that have been mentioned in previous works (Prager et al, 1971;Hermann et al, 1973;Kondo et al, 1982). After being reduced by 2 mM DTT and trapped free sulfhydryl group with IAM, the lytic activity of dLz against M. luteus decreased as a function of reduction time ( Fig.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Investigation of the amino acid sequences of small basic proteins in many species might provide valuable information in the relation of structures and functions for those proteins, as in the case of lysozyme, [13][14][15] cystatin 16) and ovostatin. 17) It has been found that duck EW lysozyme shows a difference in amino acid sequence from chicken lysozyme.…”
mentioning
confidence: 99%
“…Duck lysozyme contains three isoforms with higher enzymatic activity than that of chicken lysozyme, which has only one isoform. [13][14][15] Cystatin from duck EW presents glycosylated and phosphorylated properties, while chicken cystatin is lacking in both properties. 16) Differences y To whom correspondence should be addressed.…”
mentioning
confidence: 99%